Country Partnership Framework for the Republic of Tajikistan for the Period of FY19-FY23 - World Bank Group (World Bank, Washington, DC, 2019)
This Country Partnership Framework (CPF) provides the main elements of the cooperation between the Republic of Tajikistan and the World Bank Group during the five years spanning FY19–23. The CPF builds on the Country Partnership Strategy (CPS) of FY15–18, and incorporates the Implementation Note (IN) for the IDA18 Risk Mitigation Regime (RMR). The overarching goal of the CPF is to support Tajikistan in adopting policies geared towards reducing poverty and promoting shared prosperity in a sustainable manner. To this end, the CPF is aligned with the National Development Strategy (NDS) and the Medium-Term Development Program (2016-20) of the Government of the Republic of Tajikistan. CPF priorities have been informed by consultations with key stakeholders.This CPF has been developed at a critical time for Tajikistan, with several external changes having opened a window of opportunity; taking advantage of these would substantially enhance the country’s growth trajectory and increase resilience. Changes include the recent opening of borders with China and Uzbekistan during 2016–17 and increased trade with Afghanistan, reversing more than a century of adverse historic developments. These developments have reopened nearby export markets and reduced the costs of trading with new markets. To succeed in this potentially transformative move towards an economy integrated with neighbors and wider markets, Tajikistan will need to address principal structural, macroeconomic, and environmental legacy issues. Going forward, fiscal constraints, persisting inequalities, and a deceleration in poverty reduction call for an urgent upgrade of policies. Adopting policies that ensure opportunity for all, allow for more openness and accountability, protect the poor, and address inequalities will reduce fragility, increase resilience, and improve citizens’ standard of living.